Greenhouse gas emissions under conservation agriculture: a synthesis of field observations on integrating conservation tillage and cover crops - Sandhya Karki; Rattan Lal; Klaus Lorenz (Acta Agriculturae Scandinavica. Section B, Soil and Plant Science, 2025)
Conservation agriculture (CA), which combines conservation tillage and cover crops (CC), has gained increasing attention for its potential to improve soil health and mitigate climate change. Yet, there is limited research on its effects on greenhouse gas (GHG) emissions. Thus, field studies across different geographic locations were synthesised to assess the impact of CA on GHG emissions compared to tilled soil without CC (control). CA did not affect methane (CH4) uptake but had variable effects on CH4 emissions. Of 90 nitrous oxide (N2O) observations, 70% demonstrated no significant difference between CA and control. Although a 6% overall reduction in N2O was observed under CA, the effect was not statistically significant. None of the analysed driving factors (soil properties, CC types, and CA duration) significantly affected N2O emissions. In contrast, CA increased carbon dioxide (CO2) emissions by 12%, especially in soil with higher SOC levels (> 20 g kg−1), under legume CCs, and during the first five years of CA adoption. However, the effect diminished with long-term CA implementation. This study highlights the complex interaction of GHG emissions with management practices and soil properties, emphasising the need for site-specific strategies and long-term monitoring under diverse field conditions to understand and optimise CA practice for GHG mitigation.